Human pharmacology of intravenous lisdexamfetamine dimesylate: abuse liability in adult stimulant abusers - Jasinski, D R; Krishnan, S (Journal of psychopharmacology (Oxford), 2009)
The objective of this study is to determine the safety, tolerability and abuse liability of single intravenous (i.v.) doses of lisdexamfetamine dimesylate (LDX) and immediate-release d-amphetamine sulphate in adult stimulant abusers compared with placebo. Adult substance abusers were enrolled in this phase I, randomized, single-centre, double-blind study. An initial cohort of three subjects was enrolled to assess safety followed by a primary cohort that consisted of nine subjects. Single i.v. doses of LDX (25 or 50 mg), immediate-release d-amphetamine sulphate (10 or 20 mg) or placebo were administered at a minimum of 48-h intervals in a single-dose, three-way crossover design. 20 mg of d-amphetamine showed significantly increased abuse-related liking scores compared with placebo (P < 0.05), whereas the liking effects of 50 mg LDX did not significantly differ from placebo. The mean C(max) of d-amphetamine was 38.9 +/- 8.1 and 105 +/- 91.4 ng/ml after the administration of 50 mg LDX and 20 mg d-amphetamine respectively. The mean T(max) of d-amphetamine was 2.51 h after the administration of 50 mg LDX and 0.82 h after the administration of 20 mg d-amphetamine. LDX was well tolerated in this population. In contrast to d-amphetamine, LDX administered intravenously did not produce significant subjective abuse-related liking scores at assessed doses.